Minimally-Invasive Surgical Approach to Congenital Dacryostenosis: Proposal for a New Protocol - Pensiero, Stefano; Diplotti, Laura; Visalli, Gianluca; Ronfani, Luca; Giangreco, Manuela; Barbi, Egidio (Frontiers in Pediatrics, 2021)
Background. Congenital dacryostenosis is one of the most common ophthalmological disorders in infants, with a high spontaneous resolution rate. In patients unresponsive to conservative treatment, the first-line approach is lacrimal drainage system probing, thought there is no clear consensus on optimal timing of surgery. The optimal treatment of patients unresponsive to primary probing is also controversial. Objectives. The aim of this study is to assess the optimal timing of probing in children with congenital dacryostenosis. Other purposes are to evaluate the efficacy of repeated probing and dacryointubation in patients unresponsive to the initial surgery without evident lacrimal outflow dysgenesis, and to determine the epidemiology of these maldevelopments. Methods. A retrospective consecutive cohort study was conducted in 625 eyes of 457 patients aged 7-48 months who underwent surgery for dacryostenosis. Patients were divided into 4 cohorts according to the timing of surgery. Data were analyzed using Fisher’s test. Results. The success rate of primary probing was high, without significant differences between cohorts. One-third of recurrences were related to maldevelopments, the other two-thirds were treated with a second probing or dacryointubation, with high success rates, that did not significantly differ between the procedures. All cases unresponsive to the second surgery were resolved with dacryointubation. Conclusions. Probing is highly effective and its outcome is not affected by timing of surgery. Nevertheless, we advocate for early intervention, in order to identify possible maldevelopments, which require more invasive management. In patients unresponsive to primary probing, without evident maldevelopments, repeated probing should still be considered as the first-line approach, since it’s less invasive but similarly effective to dacryointubation.